NUMERICAL MODELLING OF TRIAXIAL TEST USING FINITE DIFFERENCE METHOD WITH HOEK-BROWN FAILURE CRITERION - Nabila Tsamara Firtania, Muthia
Mining is an industry that has big risks so it must be planned carefully. One of the most influential factors in mine planning is rock strength. Rock strength affects slope and tunnel geometry. The rock strength parameters can be determined by conducting laboratory tests, one of which is the triaxial test. The triaxial test will produce rock strength parameters such as cohesion and friction angle. Von Karman (1911) performed a triaxial test on Carrara marble by applying different lateral stresses. From that research, it is concluded that with increasing lateral stress, the rock will be more ductile and the strength value of the rock will be greater. In this study, numerical modelling of the triaxial test will be carried out using the finite difference method (with FLAC2D) with the Hoek-Brown failure criterion. The results show that the triaxial test can be modelled numerically with the finite difference method. From numerical modelling, it can be concluded that if the lateral stress increases, the rock will become more ductile and the rock strength will increase. When compared with laboratory tests, the rock strength parameter values for laboratory tests and numerical modelling are not significantly different.